Studi Komparatif Tindak Pidana Aborsi dalam Perspektif Hukum Positif dan Hukum Pidana Islam (Imam Madzhab) - Moh. Faqih (Sharia Faculty, Kiai Haji Achmad Siddiq State Islamic University of Jember, 2020)
The rise of promiscuity and free sex is the reason for a large number of abortion perpetrators in Indonesia. In the enactment of the law stipulated in the Criminal Code (KUHP) regarding abortion, it is very clear that abortion is prohibited as well as from the perspective of Islamic law it is forbidden to abort the fetus unless there is a medical reason that an abortion must be performed. However, in the opinion of Madzhab, there is still a classification of permissibility before the blowing of the spirit and the scholars agree that it is haram to abort the fetus after blowing the spirit. The research approach used in this study is the Normative Juridical Research Method, namely the approach method used in this study is the normative juridical approach or doctrinal legal research, which is legal research that uses secondary data sources. The results of the research conducted by the author are to provide insight to readers so that they better understand the meaning of abortion and also the punishment of the perpetrators of the crime of abortion both in terms of positive law and Islamic criminal law. In finding the comparison of the punishment between positive law and Islamic criminal law lies in the age limit of the fetus that is in the content of the sanction based on Islamic criminal law, the punishment is to pay ghurrah or diyat Kamilah Dari before the blowing of the spirit or after the blowing of the spirit.